The nautiloids from the Early Carboniferous Dalle à Merocanites of Timimoun, western Algeria - Korn, Dieter; Miao, Luyi; Bockwinkel, Jürgen (European Journal of Taxonomy, 2022)
Early Carboniferous coiled nautiloids from North Africa are virtually unknown. An assemblage of nine species, all from the family Trigonoceratidae, from the Dalle à Merocanites (Tournaisian-Viséan boundary interval) of Timimoun in western Algeria is described, being the most diverse Carboniferous nautiloid assemblage known from North Africa but much less diverse than the time-equivalent assemblages from Belgium and Ireland. The assemblage consists of the species Maccoyoceras pentagonum sp. nov., Lispoceras orbis sp. nov., Thrincoceras devolvere sp. nov., Rineceras multituberculatum sp. nov., Rineceras rectangulatum sp. nov., Vestinautilus padus sp. nov., Vestinautilus concinnus sp. nov., Planetoceras destrictum sp. nov. and Planetoceras transforme sp. nov. A morphometric analysis of Maccoyoceras pentagonum sp. nov. and Lispoceras orbis sp. nov. shows that the intraspecific variation in these species is within rather narrow limits.